2018
DOI: 10.3329/bpj.v21i1.37903
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Related Risk Factors Among Clients on Combined Antiretroviral Therapy in Nigeria

Abstract: Hypertension is a major challenge in human immunodeficiency virus (HIV) infected people globally. A prospective, cross-sectional study comprising two hundred and eighteen HIV-infected patients was conducted in Antiretroviral Therapy Clinic of General Hospital, Offa between November 2015 and December, 2016. Patients' blood pressure was evaluated using Omron automated blood pressure monitor following standard procedures. Dual weight and height balance was utilized to measure the weight and height of the subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Neither physical activity nor the frequency was found to be significantly associated with hypertension in this study although those who were physically inactive had higher odds of being hypertensive (OR 1.26). However, several other studies have reported inverse association with sedentary lifestyle being a significant risk factor for hypertension and having engaged in physical activities for most days of the week to be beneficial association [ 48 - 50 ]. Regular physical activity is believed to strengthen heart muscles thereby lowering the blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Neither physical activity nor the frequency was found to be significantly associated with hypertension in this study although those who were physically inactive had higher odds of being hypertensive (OR 1.26). However, several other studies have reported inverse association with sedentary lifestyle being a significant risk factor for hypertension and having engaged in physical activities for most days of the week to be beneficial association [ 48 - 50 ]. Regular physical activity is believed to strengthen heart muscles thereby lowering the blood pressure.…”
Section: Discussionmentioning
confidence: 99%